The Potential of Bioactive Peptides from Goat Milk Kefir with Antibacterial Activity as an Antibiotic Substitute - Athillah, Dhea Yasmin; Gumilar, Jajang; Wulandari, Eka (Jurnal Ilmu Ternak Universitas Padjadjaran, 2026)
This study aims to determine the optimal incubation time for goat milk kefir that produces the highest antibacterial peptides, and to determine the antibacterial activity of purified goat milk kefir. Protein levels were determined using the microassay method. Kefir, which is known to have the best incubation time for producing the highest antibacterial activity when ultrafiltered with a 10 kDa cut-off membrane, was analyzed for its molecular weight using SDS-PAGE. The antibacterial activity was tested against pathogenic bacteria E. coli and S. aureus. The highest soluble protein content was found in kefir incubated for 36 hours, with a soluble protein content value of 2.75%. The highest antibacterial activity was observed in kefir incubated for 36 hours, with inhibition zones of 15.57 mm against E. coli and 12.10 mm against S. aureus. Goat's milk kefir purified to a molecular weight >10 kDa produced inhibition zones of 69.1 mm against E. coli and 41.3 mm against S. aureus, while goat's milk kefir with a molecular weight <10 kDa did not produce inhibition zones against pathogenic bacteria E. coli and S. aureus. Goat's milk kefir incubated for 36 hours contained six bands. At K>10, which is purified and filtered goat's milk kefir with a molecular weight > 10 kDa, three protein bands were found.